Investigating the Methods of Developing Book Reading Among the Elementary Schools Students from Their Teachers Point of View - Fariba Hanifi; Akram Karamali; Mohammad Ali Zohreei; Zahra Amini (International Review of Management and Marketing, 2017)
The main goal of the present research was to investigate the methods of developing book reading culture among the elementary schools' students in Tehran. The methodology of the present study applied descriptive research design of a survey type. The studied population were the total number of93584   elementary schools teachers in Tehran city during 2013 - 14. Number of 382 teachers were chosen from the study population through the multistage random cluster sampling method. The questionnaire which utilized as the data collection instrument has been developed by the researchers of the study. Four   main components including the name of family's culture enhancement, students personality traits, the level of teachers' scientific attitude and improvement of schools facilities and equipment were identified, categorized and confirmed after the precisely studying the previous body of researches and existent  theoretical bases. The questionnaire's validity confirmed by related experts including 10 specialists and its reliability highly reported using Cronbach's alpha coefficients of 0.95. The result showed that according to Tehran city elementary teachers' point of view each of the mentioned methods as family's culture enhancement, students' personality traits, the level of teachers' scientific attitude and improvement of schools facilities and equipment confirmed as the main ways to develop book reading among the elementary schools students. Keywords: Strategies, Promotion of Book Reading Culture, elementary schools students.